Effect of Curcuma Zanthorrhiza on Population and Infectivity of Pentalonia Nigronervosa as A Vector of Banana Bunchy Top Virus Disease - Arsi; Suparman; Yulia Pujiastuti; Chandra Irsan; Rahmatul Khaira; Harman Hamidson; Arinafril; Titi Tricahyati (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2025)
BBTV (Banana Bunchy Top Virus) is a viral disease that attacks cultivated banana plants and can cause stunting. The symptoms of BBTV disease attack on banana plants are narrowed, piled up leaves and stunted plants. The disease is caused by an insect vector. Pentalonia nigronervosa is the vector insect that transmits BBTV disease. The purpose of the research was to see the java turmeric plant as an alternative host for population growth and BBTV disease vector. The method in the study used a Randomized Group Design. This treatment consists of two treatments with 10 replications. Based on the results of research conducted on the population of P. nigronervosa experienced fluctuations, but high growth in water media. BBTV disease that attacks banana plants in each treatment has the highest incidence in the control treatment, namely, 73.33% dan the lowest disease incidence the turmeric treatment was 6.67%. The highest intensity of BBTV disease attack in the control treatment was 42.06%, while the lowest in the Javanese turmeric treatment was 1.50%. P. nigronervosa inoculated on Javanese turmeric for 72 days can suppress BBTV disease transmission. However, based on the analysis of each treatment, no significant differences were found. P. nigronervosa has the highest population in the soil medium 95.4 individuals and water medium 86.7 individuals. The population of P. nigronervosa has a good development in turmeric plants.